How engagement in occupation affects older women's adaptation to low vision - Smith, Theresa Marie (NSUWorks, 2006)
"August 2006" A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Occupational Therapy. Typescript Project Advisor : Ferol Ludwig Background and need : Prior research studies on adaptation to low vision have excluded the importance of engagement in occupation to the adaptation process. The purpose of this study was to develop a theory on how visually impaired women achieve adaptation through engagement in occupation. The theoretical framework for this study is occupational adaptation. A premise of occupational adaptation is that the occupational environment, the person, and their interaction are equally important in the adaptation process. Methodology : This qualitative study explored the reflections of seven visually impaired older women, aged 65 to 91, on their adaptation to low vision. I used grounded theory methodology to construct a theoretical model of Adaptation to Low Vision by Seven Older Women. Results : Engagement in meaningful occupations facilitates internal adaptation by increasing participants' self-esteem and motivating them to continue to find methods of doing and in getting help to participate in valued occupations or their abilities. Threats to performance initiate the process of adaptation and abilities serve to motivate participants to continue getting help and finding methods of doing their meaningful occupations. It is through the integration of losses and abilities that adaptation is achieved. Conclusions : The study adds to the knowledge base of occupational therapy by illustrating how integral engagement in occupation is to the process of adaptation. Engagement in meaningful and purposeful occupations supports adaptation to low vision and is an important component of the adaptation process. Results of the study should be considered in the treatment or program planning for the visually impaired. Rehabilitation for the visually impaired could be improved with: (a) education for clients and support persons on available services, (b) provision of opportunities for peer association, (c) use of client-centered practice, (d) training for necessary adaptive equipment, (e) home evaluations, (f) intervention at any point in the adaptation process, (g) therapist familiarity of visual impairment manifestations and effects of concurrent issues, and (h) therapeutic use of occupation to address personal occupational performance challenges.